Cocoa Territory: Decision-making Toolkit: Esmelda Suazo, Technician, CACAONICA Cooperative - International Center for Tropical Agriculture (2016)
Esmelda Suazo, technician and project coordinator at CACAONICA Cooperative, shares her experience as a facilitator of the farm-level decision-making toolkit, promoted in the cocoa farming regions of Waslala, Nicaragua, by CIAT through the CGIAR Research Program on Integrated Systems for the Humid Tropics (Humidtropics).